Volume 2: Mgmt. Low/Interm. Level Waste; Spent Fuel; Economics/Analyses for Waste Mgmt.; Radiological Characterization/Applicat 2001
DOI: 10.1115/icem2001-1212
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Spent Nuclear Fuel for Long-Term Storage and Final Disposal by Encapsulating It Into Glass-Ceramic Waste Forms

Abstract: This paper describes the research work carried out at the NSC KIPT to develop and apply a final waste form in the shape of a monolithic solid block for the containment of spent nuclear fuel. To prepare radioactive waste for long-term storage and final deep geological disposal, investigations into the development of methods of immobilizing HLW simulators in protective solid matrices are being conducted at the NSC KIPT. For RBMK spent nuclear fuel it is proposed and justified to encapsulate the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A central, fixed based volume reduction facility had provided American generators of radioactive wastes cost savings as well as less volume for disposal. Sayenko et al (2002) described the research work carried out at the NSC KIPT to develop and apply a final waste form in the shape of a monolithic solid block for the containment of spent nuclear fuel. The results from laboratory scale experiments, tests and calculation carried out so far, showed that the proposed glass-ceramic materials may be used as basic materials for manufacturing the monolithic protective block in which the spent fuel elements would be embedded with the aim of further longterm storage or final disposal.…”
Section: Decontamination and Decommissionmentioning
confidence: 99%
“…A central, fixed based volume reduction facility had provided American generators of radioactive wastes cost savings as well as less volume for disposal. Sayenko et al (2002) described the research work carried out at the NSC KIPT to develop and apply a final waste form in the shape of a monolithic solid block for the containment of spent nuclear fuel. The results from laboratory scale experiments, tests and calculation carried out so far, showed that the proposed glass-ceramic materials may be used as basic materials for manufacturing the monolithic protective block in which the spent fuel elements would be embedded with the aim of further longterm storage or final disposal.…”
Section: Decontamination and Decommissionmentioning
confidence: 99%